Analisis Evaluasi Merek Smartphone Samsung Galaxy Series A - Sabilla Anggraini; Khayatin Nupus; Syamsul Hidayat (Student Research Journal, 2024)
The aim of this research is to analyze the influence of product attributes, price, the need to seek variety and dissatisfaction on the decision to switch brands to the Samsung Galaxy series. The results of the research show that product attributes and price have a negative and significant effect on the decision to switch brands, while the need to seek variety and dissatisfaction have a positive and positive effect. significant impact on brand change decisions. In order to avoid brand switching, the company developed a marketing strategy by innovating product attributes, setting prices in accordance with consumer needs. Apart from that, Samsung's strategy is to attract potential buyers by providing attractive promotions and discounts. Companies must continuously create a brand image for Samsung brand smartphones. This is done as an effort to build a strong brand. Through a strong brand image, companies can satisfy customers and minimize customers' need to look for product variations outside of Samsung brand smartphones.